L’action collective et la perception des acteurs face à la mise en place d’équipements énergétiques: les cas de Gentilly-2 et de la centrale de cogénération de Bécancour - Étienne Lyrette (Éditions en environnement VertigO, 2006)
The supply in energy presents several challenges for the industrialized world. Several countries are at the crossroads and have to make decisions on the nature of their supply for the decades to come. An increasing number of stakeholders look forward to get involve in the debate around the energy choices of their community.  The cases of Gentilly-2 nuclear plant and the power plant of cogeneration of Bécancour (Quebec, Canada) do not make exception.  The comparison of the controversies generated by the installation of these infrastructures enables us to advance that the differences observed on the level of the mobilization of the actors of the two projects are explained mainly in the technology used.